Strongyloidiasis in the gastrointestinal biopsy - Khaled, A; Ara, N; Chawdhury, LL; Nasir, TA (Pulse, 2010)
Strongyloides stercoralis is an intestinal nematode of humans. It is estimated that tens of millions of persons are infected worldwide, although no precise estimate is available [1]. S. stercoralis is distinguished by its ability-unusual among helminths-to replicate in the human host. This capacity permits ongoing cycles of autoinfection as infective larvae are internally produced. Strongyloides can thus persist for decades without further exposure of the host to exogenous infective larvae [2]. Most infected individuals are asymptomatic, but under some conditions associated with immunocompromise, this autoinfective cycle can become amplified into a potentially fatal hyperinfection syndrome and disseminated infection [3]. Diagnosis of Strongyloides stercoralis is usually made by stool examination. Detection and diagnosis of strongyloidiasis in the gastrointestinal biopsy is relatively rare [4]. DOI: 10.3329/pulse.v3i1.6551 Pulse Vol.3(1) July 2009 p27-28